Emergence within Emergency: Kazakhstan’s Higher Education System - Robertson, Douglas; Bayetova, Nazgul (International Higher Education, 2022)
This article frames a description of Kazakhstan’s emerging higher education system in five paradoxes: nationalistic globalism; regulated nonregulation; “give to get”; communal individualism; and developmental demise. To enrich the analysis, we have made a rigorous qualitative study of major speeches and policy documents by Nursultan Nazarbayev (President, 1990–2019) and his government. The commentary occurs within the context of recent uprisings in Kazakhstan and the Russian invasion of Ukraine.